PENGUATAN SELF-ESTEEM DALAM PEMBELAJARAN MATEMATIKA MELALUI PENDEKATAN PROBLEM SOLVING - Ilham Ginanjar; Aidah Fitriah (IKIP Siliwangi, 2022)
The background of the research is the low ability of students in self-esteem, so this study has the aim of comparing the application of problem solving approaches with scientific learning in strengthening self-esteem in learning mathematics. The research method used is quasi-experimental with a population of all SMP/MTs students in West Bandung Regency, with a sample of two classes in one of the SMP/MTs in West Bandung Regency. The instrument used is in the form of a questionnaire based on the Likert scale and then the data is analyzed using the two-mean similarity test. The results showed that the significance value of the two-mean similarity test was 0.00 so that it can be concluded that the self-esteem ability of students who learn using problem solving is better than those who learn using a scientific approach at a significance level of 5%.